Public Health Center (Puskesmas) Efficiency Level In Semarang Regency Year 2014 - Eko Setiawan; Y. Titik Haryati (Economics Development Analysis Journal, 2017)
Public health centers is a technical implementation unit of Local Health Department which is responsible for conducting health efforts forh the whole society and as a first-rate health services that directly reach the whole community to achieve a healthy and prosperous society.The purpose of this study is to determine the ability of Community Health Center in managing the resources and how wide the coverage range of the Community Health Centre in district of Semarang.This study using vaariable input and output.The input which is used is consisting of four variables, they are: the number of medical personnel, the number of non-medical personnel, financing sourced from regional government budget and the number of integrated service post.. While the outputvariables are the health services towards toddlers, the immunization coverage, the number of outpatient visits and coverage of births assisted by health personnel The data used was secondary data obtained from Local Health Department in district of Semarang, Central Bureau of Statistics and other sources.From the calculation of DEA, the results are, in 18 Community Health Centers are technically efficient and 8 Community Health Centers are technically inefficient.Unit public health centers that have efficient will be comparison for puskesmas that not efficient. For public health centers inefficient technically can improve efficiency value by raising output based on the calculation on DEA. Suggested the results of the efficiency with the dea can be used as an alternative to assess the efficiency of public health centers in kabupaten semarang regularly and as one input to assess, monitor and improved performance public health centers.